Signals and Systems: With MATLAB Computing and Simulink Modeling - Karris, Steven (Orchard Publications, 2007)
This text is primarily written for junior and senior undergraduates majoring in electrical and computer engineering. You will need this text if you are a student or working professional seeking to learn and/or review the basics of the Laplace and Z-transforms, the Fast Fourier Transform (FFT), state variables, and the design of analog and digital filters. Contains many real-world examples completely solved in detail and verified with MATLAB computations and Simulink models.